2010
DOI: 10.1021/es102420r
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Phenanthrene-Degrading Bacteria after Simulated in Situ Persulfate Oxidation in Contaminated Soil

Abstract: A continuous-flow column study was conducted to investigate the long-term effects of persulfate oxidation on the abundance and activity of the indigenous microbial community and phenanthrene-degrading bacteria in contaminated soil from a former manufactured gas plant (MGP) site. Approximately six pore volumes of a 20 g/L persulfate solution were introduced into the column, followed by simulated groundwater for 500 d. Soil samples were collected from the surface of the soil bed and along the column length immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 31 publications
2
51
1
Order By: Relevance
“…Extracts containing anthracene were analyzed by HPLC with fluorescence detection as described elsewhere (35). Extracts containing anthraquinone were analyzed by HPLC on the same system but with UV detection (Applied Biosystems [Ramsey, NJ] Kratos Analytical Spectroflow 757 UV absorbance detector).…”
Section: Methodsmentioning
confidence: 99%
“…Extracts containing anthracene were analyzed by HPLC with fluorescence detection as described elsewhere (35). Extracts containing anthraquinone were analyzed by HPLC on the same system but with UV detection (Applied Biosystems [Ramsey, NJ] Kratos Analytical Spectroflow 757 UV absorbance detector).…”
Section: Methodsmentioning
confidence: 99%
“…Tsitonaki [28] showed that aerobic biodegradation of creosote compounds in soil columns recovered within 2 weeks after heat activation of persulfate concentrations as high as 30 g/L. [23] passed 6 pore volumes of a 20 g/L persulfate solution through soil columns, maintained at 40 • C for activation. This caused a 2-to 3-log reduction in total bacterial 16S rRNA and a decrease in acetate consumption.…”
Section: Srb Activitymentioning
confidence: 99%
“…Soil properties and details of samples can be found in Richardson, et al (2011). The concentration of solvent-extractable anthracene in untreated and bioreactor-treated soil was 15 and 2 mg/kg, respectively .…”
Section: Soil Samplesmentioning
confidence: 99%